Additive manufacturing for refrigerant compressors. (February 2022) - Thomas, C; Hesse, U
The requirements for compressors in refrigeration industry become more demanding each year. Requirements regarding efficiency, durability, and also the possibility / demand of dry running machines are the main driving factors. So far, the majority of compressors are mainly manufactured out of cast iron, aluminum, steel, and other metals (not including sealing elements), which lead to high costs as well as weights. The scope of this work includes a demonstration of new manufacturing methods and material choices for small-scale compressors as well as a possible transfer to even larger machines. A detailed look on the potential of different material classes and compounds will be presented. The paper also takes into consideration if the new materials have to be used for lubricated compressors or if there is even a possibility for an operation without any oil. Thermodynamic and strength limits will be pointed out as well as the potential to substitute the nowadays used metals-based components by lightweight materials.